Monomodal high density polyethylene for lids and closures
By using characteristic high-density polyethylene (HDPE) resin and asymmetric hafnium metallocene catalyst composition, the problem of difficult attribute balance of polymer resins in cold sealing applications is solved, and high yield strength, stiffness and creep resistance are achieved, while maintaining good processability and environmental stress cracking resistance.
Patent Information
- Application Number
- CN202380054537.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-05
- Filing Date
- 2023-08-04
- Publication Date
- 2025-03-11
AI Technical Summary
Existing polymer resins are difficult to balance processability, stiffness, toughness, impact strength and creep resistance in cold seal applications, resulting in the sacrifice of performance of other properties on some properties.
High-density polyethylene (HDPE) resin, which has a specific density, melt index, molecular weight distribution and comonomer distribution index, is prepared by injection molding process and is polymerized using an asymmetric hafnium metallocene catalyst composition with n-propylcyclopentadienyl ligand.
It achieves high yield strength, high stiffness and high creep resistance, while maintaining good processability and environmental stress crack resistance. It is suitable for high impact grade closures, especially in low-temperature storage containers.
Smart Images

Figure CN119604549A_ABST
Abstract
Description
Technical Field
[0001] Embodiments of the present disclosure relate to polyethylene compositions for caps and closures. More particularly, the present disclosure relates to high density polyethylene compositions for injection molded caps and closures having high yield strength, high stiffness, and high creep resistance. Background Art
[0002] Polymer resins play an important role in caps and closures (C&C) devices, providing functionality such as sealing, protection and convenience in a variety of industries such as packaging, pharmaceuticals, beverages and cosmetics. A challenging area for C&C devices is cold seal applications. Ideally, the polymer resins used in C&C devices for cold seal applications will have a balance between processability, stiffness, toughness (including environmental stress crack resistance (ESCR)), impact strength and creep resistance to obtain the package integrity required for cold seal applications.
[0003] However, there is a compromise between these factors. For example, achieving high toughness generally requires a balance between molecular weight, molecular weight distribution, comonomer amount and comonomer distribution. Resins with higher molecular weight and narrower molecular weight distribution tend to provide better impact strength. However, these resins may have reduced processability due to their higher viscosity, which may lead to challenges in molding or processing. Resins with lower amounts of comonomers may have higher yield strengths, and therefore have higher creep resistance, which is desirable in cold seal applications to ensure that closures also maintain their shape and structural integrity even under pressure. Resins with higher yield strength, high stiffness and creep resistance may have reduced ESCR or processability. Therefore, this area needs to meet the desired high stiffness and high yield strength requirements to maintain acceptable levels of processability and toughness of the polymer resin. Summary of the invention
[0004] The present disclosure provides various embodiments of polymer resins having high stiffness and high yield strength requirements while maintaining acceptable levels of processability and toughness for use in a method comprising: A method of forming a closure device comprising supplying a high density polyethylene (HDPE) having: 0.950 g / cm 3 Up to 0.960g / cm 3density; a melt index (I2) of 1.000 dg / min to 5.000 dg / min measured according to ASTM D1238 (190° C., 2.16 kg); an Mn of 25,000 to 45,000; an Mw of 80,000 to 125,000; an Mz of 180,000 to 350,000; and a molecular weight distribution Mw / Mn of 2.5 to 3.5; a molecular weight comonomer distribution index (MWCDI) of>0.2; and forming the closure device using the HDPE resin.
[0005] An example of such a closure is a screw cap. BRIEF DESCRIPTION OF THE DRAWINGS
[0006] Figure 1 Data graphs showing density versus peak melting temperature for Inventive and Comparative Examples from the Examples section according to various embodiments of the present disclosure. DETAILED DESCRIPTION
[0007] Injection molding is a process for producing caps and closures (C&C) devices by injecting molten material (e.g., polymer) into a mold. The molten material injected into the mold may be cooled so that the molten material hardens to be configured into the mold to make the article. Injection molding is a well-known process.
[0008] Injection molding can be used to make C&C devices, such as threaded bottle caps or screw caps, flip caps, dispensing tops, child-resistant caps, tamper-evident caps, and snap-on caps, to name a few. As discussed herein, when such C&C devices are used in cold seal applications, it is desirable that the polymer used to form the C&C device have both high yield strength and flexibility or processability. The present disclosure provides such polymers that can be used to form C&C devices.
[0009] The HDPE resin of the present disclosure is an HDPE resin that provides a desired balance between impact strength, yield strength, processability and stiffness, and can be used for specialized high impact grade closures, such as for cryogenic storage containers. Prior to the HDPE resin of the present disclosure, resins typically had to sacrifice processability or stiffness to obtain the desired impact strength and yield strength. The HDPE resin of the present disclosure helps improve low temperature impact resistance and tensile properties without sacrificing processability, ESCR and stiffness.
[0010] In addition, the HDPE resins of the present disclosure are unimodal resins in that the HDPE resins have a single mode or peak in their molecular weight distribution. As will be appreciated, this unimodality allows the HDPE resins of the present disclosure to exhibit more uniform properties (e.g., melt flow, etc.) and mechanical, thermal, and processing behaviors compared to polymers having a broader or bimodal molecular weight distribution.
[0011] The HDPE resin of the present disclosure can be formed using the catalyst composition discussed herein, wherein the catalyst composition comprises an asymmetric hafnium metallocene having an n-propylcyclopentadienyl ligand. The catalyst composition is a single-site metallocene catalyst for polymerizing ethylene and alpha olefins to produce HPDE resins. These catalyst compositions can be used to prepare HDPE resins having multiple desired properties as discussed herein (e.g., impact resistance, low temperature flexibility, consistent melt flow behavior leading to improved processability). The HDPE resin of the present disclosure is used in a method of forming a closed device, the method comprising supplying an HDPE resin, wherein the HDPE resin has the following properties, among others: 0.950 g / cm 3 Up to 0.960g / cm 3 density; a melt index (I2) of 1.000 dg / min to 5.000 dg / min measured according to ASTM D1238 (190° C., 2.16 kg); an Mn of 25,000 to 45,000; an Mw of 80,000 to 125,000; an Mz of 180,000 to 350,000; and a molecular weight distribution Mw / Mn of 2.5 to 3.5. The HDPE resin of the present disclosure may also include a molecular weight comonomer distribution index of>0.2; wherein the HDPE resin has a molecular weight greater than 5 kJ / m 2 Up to 15kJ / m 2 The Charpy impact value (-40°C) and the average tensile yield stress (2in / min test speed) of 3.8ksi to 4.2ksi.
[0012] The asymmetric hafnium metallocene with an n-propylcyclopentadienyl ligand can be represented by structure (I):
[0013]
[0014] Where: R 1 is n-propyl, and each X is independently a leaving group. As shown in structure (I), the cyclopentadienyl ring is R 1 The cyclopentadienyl ring is not substituted. 1 The cyclopentadienyl group is substituted and the other cyclopentadienyl ring is unsubstituted, so the metallocene can be referred to as an asymmetric hafnium metallocene.
[0015] Embodiments of the present disclosure provide that X is a leaving group. One or more embodiments provide that X is selected from alkyl, aryl, hydride and halogen. One or more embodiments provide that X is selected from halogen, (C1-C5) alkyl, CH2SiMe3 and benzyl. One or more embodiments provide that X is selected from alkyl and halogen. One or more embodiments provide that X is chlorine. One or more embodiments provide that X is methyl.
[0016] Examples of X include halogen ions, hydrides, (C1 to C 12 ) alkyl, (C2 to C 12 )alkenyl, (C6 to C 12 ) aryl, (C7 to C 20 ) alkylaryl, (C1 to C 12 ) alkoxy, (C6 to C 16 )aryloxy, (C7 to C8)alkylaryloxy, (C1 to C 12 ) fluoroalkyl, (C6 to C 12 ) fluoroalkyl and (C1 to C 12 ) heteroatom-containing hydrocarbons and their substituted derivatives; one or more embodiments include hydrides, halides, (C1 to C6) alkyls, (C2 to C6) alkenyls, (C7 to C 18 )alkylaryl, (C1 to C6)alkoxy, (C6 to C 14 ) aryloxy, (C7 to C 16 ) alkyl aryloxy, (C1 to C6) alkyl carboxylate, (C1 to C6) fluorinated alkyl carboxylate, (C6 to C 12 ) aryl carboxylate, (C7 to C 18 )alkylaryl carboxylates, (C1 to C6)fluoroalkyl, (C2 to C6)fluoroalkenyl and (C7 to C 18 ) fluoroalkylaryl; one or more embodiments include hydride, chloride, fluoride, methyl, phenyl, phenoxy, benzoyloxy, tosyl, fluoromethyl and fluorophenyl; one or more embodiments include (C1 to C 12 ) alkyl, (C2 to C 12 )alkenyl, (C6 to C 12 ) aryl, (C7 to C 20 ) alkylaryl, substituted (C1 to C 12 ) alkyl, substituted (C6 to C 12 ) aryl, substituted (C7 to C 20 ) alkylaryl and (C1 to C 12 ) containing heteroatom alkyl, (C1 to C 12 ) containing heteroatom aromatic groups and (C1 to C 12 ) containing heteroatom alkylaryl; one or more embodiments include chloride, fluoride, (C1 to C6) alkyl, (C2 to C6) alkenyl, (C7 to C 18 ) alkylaryl, halogenated (C1 to C6) alkyl, halogenated (C2 to C6) alkenyl and halogenated (C7 to C 18) alkylaryl; one or more embodiments include fluoride, methyl, ethyl, propyl, phenyl, methylphenyl, dimethylphenyl, trimethylphenyl, fluoromethyl (monofluoromethyl, difluoromethyl and trifluoromethyl) and fluorophenyl (monofluorophenyl, difluorophenyl, trifluorophenyl, tetrafluorophenyl and pentafluorophenyl).
[0017] Other non-limiting examples of X groups include amines, phosphines, ethers, carboxylates, dienes, hydrocarbon groups having 1 to 20 carbon atoms, fluorinated hydrocarbon groups (e.g., -C6F5(pentafluorophenyl)), fluorinated alkyl carboxylates (e.g., CF3C(O)O-), hydrides, halogen ions, and combinations thereof. Other examples of X ligands include alkyl groups such as cyclobutyl, cyclohexyl, methyl, heptyl, tolyl, trifluoromethyl, tetramethylene, pentamethylene, methylene, methoxy, ethoxy, propoxy, phenoxy, bis(N-methylaniline), dimethylamido, and dimethylphosphoryl, etc. In one embodiment, two or more X form a part of a fused ring or ring system. In one or more embodiments, X can be a leaving group selected from the group consisting of chloride, bromide, (C1 to C5), cyclohexyl, ... 10 ) alkyl, (C2 to C 12 ) alkenyl, carboxylate, acetylacetonate, and alcoholate. In one or more embodiments, X is methyl.
[0018] The asymmetric hafnium metallocenes with n-propylcyclopentadienyl ligands discussed herein can be prepared by contacting a hafnium complex with an alkali metal complex to prepare an asymmetric hafnium metallocene with n-propylcyclopentadienyl ligand. The asymmetric hafnium metallocenes with n-propylcyclopentadienyl ligands discussed herein can be prepared by methods for preparing known metallocenes (e.g., using conventional solvents, reaction conditions, reaction times, and isolation procedures).
[0019] Alkali metal complexes can be represented by one of the following structures:
[0020]
[0021] Where M' is lithium, sodium or potassium, and R 1 It's n-propyl.
[0022] One or more embodiments provide that the hafnium complex may be represented by one of the following structures:
[0023]
[0024] Where R 1 It's n-propyl.
[0025] One or more embodiments provide that the preparation of an asymmetric hafnium metallocene having an n-propylcyclopentadienyl ligand comprises contacting the asymmetric hafnium metallocene having an n-propylcyclopentadienyl ligand with two molar equivalents of an organomagnesium halide of formula RMg(halide) or one molar equivalent of R2Mg, wherein R is (C1-C5)alkyl, CH2SiMe3 or benzyl; and the halide is Cl or Br, to prepare an asymmetric hafnium metallocene having an n-propylcyclopentadienyl ligand of structure (I), wherein each X is a halogen, (C1-C5)alkyl, CH2SiMe3 or benzyl. One or more embodiments provide that X is (C1-C5)alkyl, CH2SiMe3 or benzyl. As used herein, all references to the Periodic Table of the Elements and its Groups refer to the NEW NOTATION as published in HAWLEY'S CONDENSED CHEMICAL DICTIONARY, Thirteenth Edition, John Wiley & Sons, Inc. (1997) (reproduced with permission from IUPAC), unless reference is made to the previous IUPAC form marked with Roman numbering (which also appears therein) or unless otherwise mentioned.
[0026] As used herein, "alkyl" includes straight chain, branched chain, and cyclic alkane radicals lacking one hydrogen. Thus, for example, CH3 ("methyl") and CH2CH3 ("ethyl") are examples of alkyl radicals.
[0027] As used herein, "alkenyl" includes straight chain, branched chain, and cyclic alkene groups lacking one hydrogen group; alkynyl includes straight chain, branched chain, and cyclic ethynyl groups lacking one hydrogen group.
[0028] As used herein, "aryl" groups include phenyl, naphthyl, pyridyl and other groups whose molecules have the ring structure characteristics of benzene, naphthylene, phenanthrene, anthracene, etc. It should be understood that "aryl" groups can be C6 to C 20 Aryl groups. For example, a C6H5 aromatic structure is a "phenyl" and a C6H42 aromatic structure is a "phenylene". An "aralkyl" group is an alkyl group with a pendant aryl group. It should be understood that an "aralkyl" group can be (C7 to C 20 ) aralkyl groups. "Alkaryl" is an aryl group having one or more pendant alkyl groups.
[0029] As used herein, "alkylene" includes straight chain, branched, and cyclic hydrocarbon groups lacking two hydrogens. Thus, CH2 ("methylene") and CH2CH2 ("ethylene") are examples of alkylene groups. Other groups lacking two hydrogen groups include "arylene" and "alkenylene".
[0030] As used herein, the term "heteroatom" includes any atom selected from the group consisting of B, Al, Si, Ge, N, P, O and S. A "heteroatom-containing group" is a hydrocarbon group containing heteroatoms and may contain one or more heteroatoms of the same heteroatom or different heteroatoms, and may contain 1 to 3 heteroatoms in a specific embodiment. Non-limiting examples of heteroatom-containing groups include groups (monovalent and divalent groups) of imines, amines, oxides, phosphines, ethers, ketones, oxazoline heterocycles, oxazolines and thioethers.
[0031] As used herein, the term "substituted" means that one or more hydrogen atoms in the parent structure have been independently replaced with a substituent atom or group.
[0032] The asymmetric hafnium metallocene with n-propylcyclopentadienyl ligand discussed herein can be used to prepare catalyst compositions (e.g., injection molding compositions). These compositions include the asymmetric hafnium metallocene discussed herein and an activator. The asymmetric hafnium metallocene discussed herein can be contacted with an activator to prepare a catalyst composition. One or more embodiments provide that the activator is an alkylaluminoxane, such as methylaluminoxane. As used herein, "activator" refers to any supported or unsupported compound or combination of compounds, which can activate a complex or catalyst component, such as by generating a cationic species of a catalyst component. For example, this can include capturing at least one leaving group, such as the "X" group described herein, from the metal center of a complex / catalyst component (e.g., an asymmetric hafnium metallocene with n-propylcyclopentadienyl ligand of structure (I)). An activator may also be referred to as a "co-catalyst". As used herein, "leaving group" refers to one or more chemical moieties that are combined with a metal atom and can be captured by an activator, thereby generating a substance that is active for olefin polymerization. Various catalyst compositions, for example, olefin polymerization catalyst compositions are known in the art, and different known catalyst composition components can be used. Different amounts of known catalyst composition components can be used for different applications.
[0033] The asymmetric hafnium metallocene with n-propylcyclopentadienyl ligand discussed herein can be used to prepare a spray-dried composition. As used herein, a "spray-dried composition" refers to a composition comprising a number of components that has undergone a spray-drying process. Various spray-drying processes are known in the art and are suitable for forming the spray-dried composition disclosed herein. One or more embodiments provide that the spray-dried composition comprises a modified composition.
[0034] In one or more embodiments, the spray drying process may include atomizing a composition comprising an asymmetric hafnium metallocene with an n-propylcyclopentadienyl ligand discussed herein. Many other known components may be used in the spray drying process. Atomizers such as atomizing nozzles or centrifugal high-speed disks may be used, for example, to produce a spray or dispersion of composition droplets. The droplets of the composition may then be rapidly dried by contact with an inert dry gas. The inert dry gas may be any gas that is not reactive under the conditions employed during atomization, such as nitrogen. The inert dry gas may encounter the composition at the atomizer, which produces a droplet stream on a continuous basis. The dried composition particles may be captured from the process in a separator such as a cyclone separator, which may separate the formed solid from a gas mixture of a drying gas, a solvent, and other volatile components.
[0035] For example, the spray-dried composition can have a free-flowing powder form. After the spray-drying process, the spray-dried composition and many known components can be used to form a slurry. The spray-dried composition can be used together with a diluent to form a slurry suitable for, for example, olefin polymerization. In one or more embodiments, the slurry can be combined with one or more additional catalysts or other known components before being delivered to a polymerization reactor.
[0036] In one or more embodiments, the spray-dried composition can be formed by contacting spray-dried activator particles (such as spray-dried MAO) with a solution of an asymmetric hafnium metallocene with an n-propylcyclopentadienyl ligand as discussed herein. Such solutions can typically be prepared in, for example, an inert hydrocarbon solvent, and are sometimes referred to as a conditioning solution. Such spray-dried compositions comprising contacting a conditioning solution of an asymmetric hafnium metallocene with an n-propylcyclopentadienyl ligand with spray-dried activator particles (such as spray-dried MAO) can be prepared in situ in the feed line to a gas phase polymerization reactor by contacting the conditioning solution with a slurry of spray-dried activator particles (typically in mineral oil).
[0037] Various spray drying conditions can be used for different applications. For example, the spray drying process can utilize a drying temperature of 75° C. to 185° C. Other drying temperatures are also possible, wherein the temperature can depend on the metallocene and activator particles. Various sizes of the orifice of the atomizing nozzle used during the spray drying process can be used to obtain different particle sizes. Alternatively, for other types of atomizers such as disks, the rotation speed, disk size, and number / size of holes can be adjusted to obtain different particle sizes. One or more embodiments provide that fillers can be used in the spray drying process. Different fillers and their amounts can be used for various applications.
[0038] The asymmetric hafnium metallocene with n-propylcyclopentadienyl ligand discussed herein (e.g., injection molding composition, such as spray-dried hafnium metallocene composition) can be used to prepare polymers. For example, the asymmetric hafnium metallocene with n-propylcyclopentadienyl ligand can be activated (i.e., activated with an activator) to prepare a catalyst. One or more embodiments provide that the spray-dried composition comprises an activator. As used herein, "activator" refers to any supported or unsupported compound or combination of compounds, which can activate the complex or catalyst component, such as by generating a cationic species of the catalyst component, for example, to provide a catalyst. The activator may also be referred to as a "cocatalyst". The activator may include a Lewis acid or a non-coordinating ion activator or an ionizing activator, or any other compound including a Lewis base, an alkyl aluminum and / or a conventional cocatalyst. The activator includes methylaluminoxane (MAO) and modified methylaluminoxane (MMAO), etc. One or more embodiments provide that the activator is methylaluminoxane. Activation conditions are well known in the art. Known activation conditions can be used.
[0039] The molar ratio of the metal (e.g., aluminum) in the activator to the hafnium in the asymmetric hafnium metallocene with n-propylcyclopentadienyl ligands can be 1500: 1 to 0.5: 1, 300: 1 to 1: 1, or 150: 1 to 1: 1. One or more embodiments provide that the molar ratio of the activator to the hafnium in the asymmetric hafnium metallocene with n-propylcyclopentadienyl ligands is at least 75: 1. One or more embodiments provide that the molar ratio of the activator to the hafnium in the asymmetric hafnium metallocene with n-propylcyclopentadienyl ligands is at least 100: 1. One or more embodiments provide that the molar ratio of the activator to the hafnium in the asymmetric hafnium metallocene with n-propylcyclopentadienyl ligands is at least 150: 1.
[0040] The asymmetric hafnium metallocene with n-propylcyclopentadienyl ligand discussed herein and many other components can be loaded on the same or separate carriers, or one or more of these components can be used in an unloaded form. The use of the carrier can be achieved by any technology used in the art. One or more embodiments provide that a spray drying process is utilized. The carrier can be functionalized. One or more embodiments provide that the spray-dried composition comprises a carrier.
[0041] "Carrier" may also be referred to as "support", and refers to any carrier material, including porous carrier materials (such as talc), inorganic oxides and inorganic chlorides. Other carrier materials include resin carrier materials (e.g., polystyrene), functionalized or cross-linked organic carriers (such as polystyrene divinyl benzene polyolefins or polymeric compounds), zeolites, clays or any other organic or inorganic carrier materials, etc., or mixtures thereof.
[0042] The support material includes an inorganic oxide including a Group 2, 3, 4, 5, 13 or 14 metal oxide. Some preferred supports include silica, fumed silica, alumina, silica-alumina and mixtures thereof. Some other supports include magnesium oxide, titanium oxide, zirconium oxide, magnesium chloride, montmorillonite, phyllosilicates, zeolites, talc, clays and the like. Moreover, combinations of these support materials may be used, such as silica-chromium, silica-alumina, silica-titania and the like. One or more embodiments provide that the support is silica, and one or more embodiments provide that the support is hydrophobic fumed silica. One or more embodiments provide that the support is dehydrated silica. Additional support materials may include porous acrylic polymers, nanocomposites, aerogels, spherulites and polymer beads. An example of a support is available under the trade name Cabosil TM Fumed silica obtained from TS-610, or other TS-series or TG-series supports available from Cabot Corporation. Fumed silica is typically silica having a particle size of 7 to 30 nanometers that has been treated with dimethylsilyl dichloride such that most of the surface hydroxyl groups are capped.
[0043] The asymmetric hafnium metallocene with n-propylcyclopentadienyl ligand discussed herein (e.g., injection molding composition / catalyst composition / spray drying composition) and olefins can be contacted under polymerization conditions to prepare a polymer, for example, a HDPE resin of the present disclosure. The polymerization process can be a suspension polymerization process, a slurry polymerization process, and / or a gas phase polymerization process. The polymerization process can utilize known equipment and reaction conditions, such as known polymerization conditions. The polymerization process is not limited to any particular type of polymerization system. The polymer can be used in a variety of articles, such as injection molded articles, for example, a cap or closure device, such as a screw cap for a container.
[0044] One or more embodiments provide for the use of a gas phase reactor system to prepare the polymer. One or more embodiments provide for the use of a single gas phase reactor, for example, as opposed to a series of reactors. In other words, the polymerization reaction occurs in only one reactor. For example, a fluidized bed reactor may be used to prepare the polymer. Gas phase reactors are known, and known components can be used in fluidized bed reactors.
[0045] As used herein, "olefins" which may be referred to as "alkenes" refer to linear, branched or cyclic compounds including carbon and hydrogen and having at least one double bond. As used herein, when polyolefins, polymers and / or copolymers are referred to as comprising olefins (e.g., prepared by olefins), the olefins present in such polymers or copolymers are olefins in polymerized form. For example, when it is said that the ethylene content of the copolymer is 75% to 95% by weight, it is understood that the polymer units in the copolymer are derived from ethylene in the polymerization reaction, and based on the gross weight of the polymer, the derived units are present in 75% to 95% by weight. High-grade alpha-olefins refer to alpha-olefins with 3 or more carbon atoms.
[0046] The polyolefins prepared using the compositions discussed herein can be prepared from olefin monomers, such as ethylene (i.e., polyethylene), and straight or branched higher alpha-olefin monomers containing 3 to 20 carbon atoms. Examples of higher alpha-olefin monomers include, but are not limited to, propylene, butene, pentene, 1-hexene, and 1-octene. Examples of polyolefins include ethylene-based polymers with at least 50% by weight of ethylene, including ethylene-1-butene, ethylene-1-hexene, and ethylene-1-octene copolymers, etc. One or more embodiments provide that, based on the gross weight of the polymer, the polymer may include 50% by weight to 99.9% by weight of units derived from ethylene. All individual values and subranges from 50 wt % to 99.9 wt % are included; for example, based on the total weight of the polymer, the polymer may include a lower limit of 50 wt %, 60 wt %, 70 wt %, 80 wt % or 90 wt % of units derived from ethylene to an upper limit of 99.9 wt %, 99.7 wt %, 99.4 wt %, 99 wt %, 96 wt %, 93 wt %, 90 wt % or 85 wt % of units derived from ethylene. Based on the total weight of the polymer, the polymer may include 0.1 wt % to 50 wt % of units derived from comonomers. One or more embodiments provide that ethylene is used as a monomer and hexene is used as a comonomer.
[0047] As mentioned, polymers prepared using the compositions disclosed herein can be prepared in a fluidized bed reactor. The fluidized bed reactor can have a reaction temperature of 10°C to 130°C. All individual values and subranges from 10°C to 130°C are included; for example, the fluidized bed reactor can have a reaction temperature of 10°C, 20°C, 30°C, 40°C, 50°C, or 55°C at a lower limit to 130°C, 120°C, 110°C, 100°C, 90°C, 80°C, 70°C, or 60°C at an upper limit.
[0048] The fluidized bed reactor can have an ethylene partial pressure of 30 pounds per square inch (psi) to 250 psi, including all individual values and subranges from 30 to 250; for example, the fluidized bed reactor can have an ethylene partial pressure of 30 psi, 45 psi, 60 psi, 75 psi, 85 psi, 90 psi, or 95 psi on the lower limit and 250 psi, 240 psi, 220 psi, 200 psi, 150 psi, or 125 psi on the upper limit.
[0049] One or more embodiments provide that ethylene is used as a monomer and hexene is used as a comonomer. The fluidized bed reactor can have a comonomer to ethylene molar ratio of 0.0001 to 0.100, for example, C6 / C2. All individual values and subranges from 0.0001 to 0.100 are included; for example, the fluidized bed reactor can have a comonomer to ethylene molar ratio of 0.0001, 0.0005, 0.0007, 0.001, 0.0015, 0.002, 0.007, or 0.010 to an upper limit of 0.100, 0.080, or 0.050.
[0050] When hydrogen is used in the polymerization process, the fluidized bed reactor can have, for example, a hydrogen to ethylene molar ratio (H2 / C2) of 0.00001 to 0.90000. All individual values and subranges from 0.00001 to 0.90000 are included; for example, the fluidized bed reactor can have a H2 / C2 with a lower limit of 0.00001, 0.00005, or 0.00008 to an upper limit of 0.90000, 0.500000, 0.10000, 0.01500, 0.00700, or 0.00500. One or more embodiments provide that hydrogen is not utilized.
[0051] The comonomer distribution or short chain branching distribution in ethylene / α-olefin copolymers can be characterized as normal (also known as having a Ziegler-Natta distribution), reverse (also known as having a broad orthogonal composition distribution (BOCD)), or flat. Several reported methods are used to quantify BOCD. In this article, a simple straight line fit is used so that the normal or reverse nature of the comonomer distribution can be quantified by the molecular weight comonomer distribution index (MWCDI), which is the slope of the linear regression of the comonomer distribution measured by composition GPC, where the x-axis is Log (MW) and the y-axis is the weight percentage of the comonomer. Short chain branching (SCB) is excluded from the MWCDI calculation according to the formula 0.1> (SCBF) * (MW detector response), where SCBF is the SCB frequency measured as SCB / 1000C. Reverse comonomer distribution is defined when MWCDI>0, and normal comonomer distribution is defined when MWCDI<0. When MWCDI=0, the comonomer distribution is said to be flat. In addition, MWCDI quantifies the magnitude of the comonomer distribution. Comparing two polymers with MWCDI>0, the polymer with the larger MWCDI value is defined as having a larger, i.e., increased BOCD; in other words, the polymer with the larger MWCDI value has a larger reverse comonomer distribution. A polymer with a relatively large MWCDI (i.e., BOCD) can provide one or more improved physical properties compared to a polymer with a relatively small MWCDI.
[0052] The polyolefins prepared using the compositions disclosed herein are unimodal, for example, as opposed to bimodal. As used herein, "unimodal" refers to a polymer that can be characterized by having one peak (one maximum) in a GPC chromatogram showing a molecular weight distribution. In addition, a unimodal composition is a composition prepared by using a single catalyst (e.g., a single polyethylene catalyst) in a single reactor. This distinguishes a unimodal composition as defined above from a bimodal composition that may have one peak in a GPC chromatogram showing a molecular weight distribution. These bimodal compositions are those prepared by one or more polyethylene catalysts in a graded reactor process, which is typically a dual reactor process, including but not limited to two solution polyethylene reactors or two gas phase polymer reactors or two slurry phase polymerization reactors or a combination thereof (such as a sequential slurry phase and a gas phase reactor), so that two different polymers of different densities and optional molecular weights are prepared in different reactors. In addition, two or more PE catalysts in a single solution, slurry or gas phase reactor can produce a bimodal polymer that may have a single peak in a GPC chromatogram showing a molecular weight distribution as described above. This is also defined as a bimodal polymer composition.
[0053] The HDPE resin prepared using the compositions disclosed herein can have a MWCDI greater than 0.2 (>0.2). For example, the HDPE resin prepared using the compositions disclosed herein can have a MWCDI of greater than 0.2 to 5. All individual values and subranges from 0.2 to 5 are included; for example, the HDPE resin can have a MWCDI with a lower limit of 0.2, 0.5, or 1 to an upper limit of 5, 4, 3.5, or 3.
[0054] The HDPE resin prepared using the compositions disclosed herein can have a polydispersity composition index (PCI) greater than 5 (>5). For example, the HDPE resin prepared using the compositions disclosed herein can have a PCI of greater than 5 to 40. All individual values and subranges from 5 to 40 are included; for example, the HDPE resin can have a PCI with a lower limit of 5, 7, or 10 to an upper limit of 40, 30, 25, or 20. The PCI provides a metric to weight the MWCDI of the HDPE resin by Mw / Mn to better distinguish between unimodal and bimodal samples, as provided in the Examples section herein, and is calculated according to the following equation: PCI = [MWCDI / (Mw / Mn)]×100.
[0055] The HDPE resin prepared using the composition disclosed herein may have a hardness of 0.950 g / cm 3 Up to 0.960g / cm 3 Density. Including 0.950g / cm 3 Up to 0.960g / cm 3 All individual values and subranges of; for example, HDPE resin may have a lower limit of 0.950 g / cm 3 , 0.951g / cm 3 or 0.952 g / cm 3 The upper limit is 0.960g / cm 3 or 0.958 g / cm 3 The density can be determined according to ASTM D792.
[0056] The HDPE resin prepared using the composition disclosed herein can have an ESCR F of 20 hours to 50 hours. 50 . Includes all individual values and subranges from 20 hours to 50 hours; for example, a HDPE resin may have an ESCR F with a lower limit of 20 hours, 22 hours, or 30 hours and an upper limit of 50 hours, 45 hours, or 40 hours. 50 ESCR F can be measured according to ASTM D-1693, Condition B, in a 10 vol% aqueous Igepal CO-630 solution. 50 .
[0057] The HDPE resin prepared using the composition disclosed herein can have a tensile secant modulus at 2% of 110 ksi to 140 ksi. All individual values and subranges from 110 ksi to 140 ksi are included; for example, the HDPE resin can have a tensile secant modulus at 2% with a lower limit of 110 ksi, 115 ksi, or 120 ksi to an upper limit of 140 ksi, 130 ksi, or 125 ksi. The tensile secant modulus at 2% can be determined according to ASTM D638.
[0058] The HDPE resin prepared using the composition disclosed herein can have a melt index (I2) of 1.000 dg / min to 5.000 dg / min. I2 can be measured according to ASTM D1238 (190°C, 2.16 kg). All individual values and subranges from 1.000 dg / min to 5.000 dg / min are included; for example, the HDPE resin can have an I2 with a lower limit of 1.000 dg / min, 1.200 dg / min, 1.400 dg / min, or 1.6000 dg / min to an upper limit of 5.000 dg / min, 4.000 dg / min, 3.500 dg / min, or 3.000 dg / min.
[0059] The HDPE resin prepared using the composition disclosed herein may have a melt index (I) of 10 dg / min to 100 dg / min. 21 ). It can be measured according to ASTM D1238 (190°C, 21.6kg). 21 dg / min, 10 dg / min, 15 dg / min, 20 dg / min, 25 dg / min, or 30 dg / min, and an upper limit of 100 dg / min, 90 dg / min, 80 dg / min, 70 dg / min, or 60 dg / min. 21 .
[0060] The HDPE resin prepared using the composition disclosed herein may have a melt index (I) of 5 dg / min to 40 dg / min. 10 ). It can be measured according to ASTM D1238 (190°C, 10kg). 10 . Including all individual values and subranges from 5 dg / min to 40 dg / min; for example, the HDPE resin may have an I of 5 dg / min, 6 dg / min, 7 dg / min, 8 dg / min, or 9 dg / min and an I of 40 dg / min, 35 dg / min, 30 dg / min, or 25 dg / min. 10 .
[0061] The HDPE resin prepared using the catalyst composition disclosed herein can have a weight average molecular weight (Mw) of 80,000 g / mol to 125,000 g / mol. All individual values and subranges of 80,000 g / mol to 125,000 g / mol are included; for example, the HDPE resin can have a Mw with a lower limit of 80,000 g / mol, 90,000 g / mol, 92,500 g / mol, 93,500 g / mol, or 95,000 g / mol to an upper limit of 125,000 g / mol, 120,000 g / mol, 110,000 g / mol, or 100,000 g / mol. As known in the art, Mw can be determined by gel permeation chromatography (GPC). GPC is discussed herein.
[0062] The HDPE resin prepared using the composition disclosed herein can have a number average molecular weight (Mn) of 25000 g / mol to 45000 g / mol. All individual values and subranges of 25000 g / mol to 45000 g / mol are included; for example, the HDPE resin can have a lower limit of 25000 g / mol, 27000 g / mol, 28000 g / mol, 29000 g / mol, or 30000 g / mol to an upper limit of 45000 g / mol, 42000 g / mol, 40000 g / mol, 38000 g / mol, or 35000 g / mol. Mn can be determined by GPC as discussed herein.
[0063] The HDPE resin prepared using the composition disclosed herein can have a Z average molecular weight (Mz) of 180,000 g / mol to 350,000 g / mol. All individual values and subranges from 180,000 g / mol to 350,000 g / mol are included; for example, the HDPE resin can have a lower limit of 180,000 g / mol, 190,000 g / mol, or 200,000 g / mol to an upper limit of 350,000 g / mol, 300,000 g / mol, or 250,000 g / mol. Mz can be determined by GPC.
[0064] The HDPE resin prepared using the composition disclosed herein can have a maximum peak molecular weight (Mp) of 60,000 g / mol to 90,000 g / mol. All individual values and subranges of 60,000 g / mol to 90,000 g / mol are included; for example, the HDPE resin can have a Mp with a lower limit of 60,000 g / mol, 65,000 g / mol, or 70,000 g / mol to an upper limit of 90,000 g / mol, 85,000 g / mol, or 80,000 g / mol. Mp can be determined by GPC.
[0065] The HDPE resin prepared using the composition disclosed herein can have a weight average molecular weight to number average molecular weight ratio (Mw / Mn) of 2.5 to 3.5. All individual values and subranges from 2.5 to 3.5 are included; for example, the HDPE resin can have a Mw / Mn with a lower limit of 2.5, 2.55, or 2.6 and an upper limit of 3.5, 3.25, or 3.0. Mw / Mn can also be referred to as molecular weight distribution or "MWD".
[0066] The HDPE resin prepared using the composition disclosed herein can have an average tensile yield stress (2in / min) of 3.8 ksi to 4.2 ksi. All individual values and subranges from 3.8 ksi to 4.2 ksi are included; for example, the HDPE resin can have an average tensile yield stress of 3.800 ksi, 3.850 ksi, or 3.900 ksi to an upper limit of 4.2 ksi, 4.1 ksi, or 4.0 ksi. The average tensile yield stress is determined using ASTM D638.
[0067] The HDPE resin prepared using the compositions disclosed herein can have a peak melting point (Tm) greater than 132° C. For example, the HDPE resin prepared using the compositions disclosed herein can have a peak melting point (Tm) greater than 132° C. to 135° C. The peak melting point can be determined as discussed herein.
[0068] The HDPE resin prepared using the compositions disclosed herein can have a tensile yield strain (2 in / min) of 9% to 11%. All individual values and subranges from 9% to 11% are included; for example, the HDPE resin can have a tensile yield strain of 9% to 10% or 10% to 11%. The tensile yield strain is determined using ASTM D638.
[0069] The HDPE resin prepared using the compositions disclosed herein may have an average flexural modulus (0.05 in / min) of 150 ksi to 200 ksi. All individual values and subranges of 150 ksi to 200 ksi are included; for example, the HDPE resin may have an average flexural modulus (0.05 in / min) with a lower limit of 150, 160, or 170 to an upper limit of 200, 190, or 180. In one embodiment, the HDPE resin prepared using the compositions disclosed herein may have an average flexural modulus (0.05 in / min) of 170 ksi to 180 ksi. The average flexural modulus (0.05 in / min) is measured according to ASTM D790.
[0070] The HDPE resin prepared using the composition disclosed herein can have an average flexural modulus (0.5 in / min) of 190 ksi to 230 ksi. All individual values and subranges from 190 ksi to 230 ksi are included; for example, the HDPE resin can have an average flexural modulus (0.5 in / min) with a lower limit of 190, 200, or 210 to an upper limit of 230, 225, or 220. The average flexural modulus (0.5 in / min) is measured according to ASTM D790.
[0071] The HDPE resin prepared using the composition disclosed herein can have a flexural secant modulus at 2% (0.05 in / min) of 100 kilopounds per square inch (ksi) to 140 ksi. All individual values and subranges from 100 ksi to 140 ksi are included; for example, the HDPE resin has a flexural secant modulus at 2% with a lower limit of 100 ksi, 105 ksi, or 110 ksi to an upper limit of 140 ksi, 130 ksi, or 120 ksi. The flexural secant modulus at 2% (0.05 in / min) can be determined according to ASTM D790.
[0072] The HDPE resin prepared using the composition disclosed herein can have a flexural secant modulus at 2% (0.5 in / min) of 120 kilopounds per square inch (ksi) to 170 ksi. All individual values and subranges from 120 ksi to 170 ksi are included; for example, the HDPE resin can have a flexural secant modulus at 2% with a lower limit of 120 ksi, 130 ksi, or 140 ksi to an upper limit of 170 ksi, 165 ksi, or 160 ksi. The flexural secant modulus at 2% (0.5 in / min) can be determined according to ASTM D790.
[0073] The HDPE resin prepared using the composition disclosed herein can have a thermal conductivity greater than 5 kJ / m 2 Up to 15kJ / m 2 Charpy impact value (-40℃). Including 5kJ / m 2 Up to 15kJ / m 2 All individual values and subranges of; for example, HDPE resin may have a lower limit of 5 kJ / m 2 , 6kJ / m 2 or 7 kJ / m 2 Up to 15 kJ / m 2 、14kJ / m 2 or 12 kJ / m 2 Charpy impact strength (-40°C) is tested according to ISO 179.
[0074] The HDPE resin prepared using the compositions disclosed herein can be advantageously used in injection molding or compression molding processes to form closures, such as the screw caps discussed herein, etc. The injection molding or compression molding process can include feeding the HDPE resin into a heated barrel with a rotating screw that promotes melting and homogenization of the HDPE resin, followed by injecting the molten HDPE resin (110° C. to 400° C.) under high pressure into a mold cavity in the shape of the desired closure. After the mold cavity is filled, the HDPE resin in the shape of the closure is allowed to cool before the mold is opened to release the closure. The resulting closure can then be subjected to post-processing operations as desired, such as trimming excess material or removing any gates, runners, or flash. Depending on the specific requirements of the closure, additional processes such as surface finishing, painting, or assembly may be performed.
[0075] Various aspects of the disclosure are provided as follows.
[0076] Aspect 1 provides a method for forming a closure device, the method comprising: supplying a high-density polyethylene (HDPE) having: 0.950 g / cm 3 Up to 0.960g / cm 3 density; a melt index (I2) of 1.000 dg / min to 5.000 dg / min measured according to ASTM D1238 (190°C, 2.16 kg); a Mn of 25,000 to 45,000; a Mw of 80,000 to 125,000; a Mz of 180,000 to 350,000; and a molecular weight distribution Mw / Mn of 2.5 to 3.5; a molecular weight comonomer distribution index (MWCDI) of >0.2; and the closure device is formed using the HDPE resin. Aspect 2 provides that for aspect 1, the HDPE resin has a molecular weight greater than 5 kJ / m 2 Up to 15kJ / m 2Aspect 3 provides that, for any of Aspects 1 to 2, the HDPE has a peak melting temperature (Tm) greater than 132°C. Aspect 4 provides that, for any of Aspects 1 to 3, the HDPE has an average tensile yield stress (2 in / min test speed) of 3.8 ksi to 4.2 ksi. Aspect 5 provides that, for any of Aspects 1 to 4, the HDPE resin has an environmental stress crack resistance (ESCR) Condition B (F50, 10%) of 20 hours to 50 hours. Aspect 6 provides any of Aspects 1 to 5, wherein the HDPE resin has a tensile secant modulus at 2% of 110 ksi to 140 ksi. Aspect 7 provides any of Aspects 1 to 6, wherein the HDPE resin has a tensile yield strain (2 in / min) of 9% to 11%. Aspect 8 provides any of Aspects 1 to 7, wherein the HDPE resin has an average flexural modulus (0.05 in / min) of 150 ksi to 200 ksi. Aspect 9 provides any one of Aspects 1 to 7, wherein the HDPE resin has an average flexural modulus (0.5 in / min) of 190 ksi to 230 ksi. Aspect 10 provides any one of Aspects 1 to 7, wherein the HDPE resin has a flexural secant modulus (0.05 in / min) at 2% of 100 ksi to 140 ksi. Aspect 11 provides any one of Aspects 1 to 7, wherein the HDPE resin has a flexural secant modulus (0.5 in / min) at 2% of 120 ksi to 170 ksi. Aspect 12 provides any one of Aspects 1 to 11, wherein the HDPE resin has a melt index (I) of 5 dg / min to 40 dg / min measured according to ASTM D1238 (190° C., 10 kg). 10 ). Aspect 13 provides according to any one of aspects 1 to 10, wherein the HPDE resin has a polydispersity composition index (PCI) >5. Aspect 14 provides according to any one of aspects 1 to 13, wherein forming the closed device includes compression molding or injection molding the HDPE resin to form the closed device. Aspect 15 provides a method for preparing the HDPE resin according to any one of aspects 1 to 14, the method comprising: preparing a catalyst composition using an asymmetric hafnium metallocene; and contacting the catalyst composition with ethylene and a comonomer optionally selected from the group consisting of propylene and (C4-C20) α-olefins to prepare the HDPE resin. Aspect 16 provides a method for preparing the HDPE resin according to any one of aspects 1 to 14, the method comprising: preparing a catalyst composition using an asymmetric hafnium metallocene having an n-propylcyclopentadienyl ligand represented by structure (I):
[0077]
[0078] Where R 1 n-propyl; and each X is independently a leaving group; and the catalyst composition is contacted with ethylene and optionally a comonomer selected from the group consisting of propylene and (C4-C20) α-olefins to produce the HDPE resin. Aspect 17 provides a closure device formed by any one of aspects 1 to 16. Aspect 18 provides that for aspect 17, the closure device is a screw cap.
[0079] Example
[0080] Synthesis of (n-propylcyclopentadienyl)hafnium(IV)trichloride (dimethoxyethane adduct (adduct))
[0081] (n-propylcyclopentadienyl)hafnium(IV) trichloride (dimethoxyethane adduct (adduct)) is represented by the following formula:
[0082]
[0083] And synthesized by adjusting the procedure described in Harlan's WO2016 / 168448A1. In a 100mL round-bottom flask, bis(n-propylcyclopentadienyl)hafnium dichloride (25.1g, 54.1mmol) was heated to 140°C until melted. HfCl4 (17.5g, 54.6mmol) in the form of solid powder was added to the flask. The contents were heated at 140°C for about 30 minutes and a brown viscous liquid was formed. The 100mL round-bottom flask was attached to a short-path distillation apparatus, which consisted of a glass tube (90° bend) attached to a Schlenk flask. The stopcock of the Schlenk flask was evacuated on the assembly. Distillation was performed from 105°C to 110°C under a vacuum of 0.4 Torr. In about an hour, most of the material was distilled / sublimated into the Schlenk flask or retained in the glass tube. The solid material in the U-tube was scraped out and combined with the material in the Schlenk flask. To the solid was added toluene (50 mL) and dimethoxyethane (50 mL). It was heated to reflux to form a solution, and toluene (50 mL) was added. Colorless needles were formed after cooling. Pentane (200 mL) was added to allow further solid precipitation to form. The solid was isolated by filtration, washed with pentane (2×50 mL) and dried under vacuum to provide an adduct (42.2 g); the combined supernatant and washings were cooled to obtain an additional 2.6 g of adduct, which was isolated. Total yield = 44.8 g (86%).
[0084] Synthesis of (n-propylcyclopentadienyl)(cyclopentadienyl)hafnium(IV) dichloride
[0085] (n-propylcyclopentadienyl)(cyclopentadienyl)hafnium(IV)dichloride ((n-PrCp)(Cp)HfCl2):
[0086]
[0087] Preparation is as follows. In a glove box, 0.75 grams (1.56 mmoles) of (n-propylcyclopentadienyl) hafnium (IV) trichloride (dimethoxyethane adduct (gray solid)) was added to an oven-dried 4 ounce glass bottle. A Teflon-coated stirring bar and 40 mL of dry toluene were added to the adduct, and the contents of the bottle were stirred via magnetic stirring to form a slurry. The slurry was gray and turbid. One (1) molar equivalent of cyclopentadienyl lithium (CpLi) (white solid) was then slowly added to the slurry, and then stirred overnight at room temperature (20°C). NMR spectra showed the formation of the desired product with some unreacted starting material. The mixture was allowed to stir at room temperature for another 5 hours. The entire reaction mixture was filtered and volatiles were removed from the filtrate under reduced pressure. The solid was recrystallized from warm hexane and toluene. 0.419 g of a light gray solid was isolated (total yield after recrystallization was 63.9%). 1 H and 13 C NMR spectroscopy confirmed the desired product. 1 H NMR (400 MHz, benzene-D6) δ 5.86 (s, 3H), 5.77–5.72 (m, 2H), 5.57 (t, J = 2.7 Hz, 2H), 2.63–2.54 (m, 2H), 1.48–1.35 (m, 2H), 0.80 (t, J = 7.3 Hz, 3H). 13 C NMR (101 MHz, benzene-d6) δ 132.81, 115.78, 114.13, 110.86, 32.38, 24.34, 14.00.
[0088] Preparation of spray-dried hafnocene catalyst (IE 1)
[0089] The spray dried hafnocene catalyst (IE 1) was prepared as follows. The spray dried hafnocene catalyst was made of (n-propylcyclopentadienyl)(cyclopentadienyl) hafnium (IV) dichloride and a support material. 2.38 lb of hydrophobic fumed silica ( TS-610) and 37.0 lb of 10 wt% methylaluminoxane (MAO) in toluene. To the mixture was added 80.0 g of (n-propylcyclopentadienyl)(cyclopentadienyl)hafnium(IV) dichloride and an additional 20 lb of toluene, added to the contents of the vessel while mixing. The contents of the vessel were then spray dried (inlet temperature 146°C; 84°C outlet temperature; 14 lb / hr slurry inlet feed, 20,000 rpm atomizer speed) to provide 4.1 lbs of spray dried hafnocene catalyst (IE 1) in powder form.
[0090] The polymerization is performed as follows. The polymerization uses a pilot fluidized bed gas phase polymerization reactor, which includes a reactor vessel containing a fluidized bed of ethylene / alpha-olefin copolymer powder, and a distributor plate disposed above the bottom head, and a bottom gas inlet is defined at the top of the reactor vessel and has an expansion section or a cyclone system to reduce resin fines that may escape from the fluidized bed. The expansion section defines a gas outlet. The reactor further includes a compression blower for passing a continuous circulating gas from the gas outlet in the expansion section at the top of the reactor vessel downward to and into the bottom gas inlet of the reactor through a circulation loop, and flows through a distributor plate and a fluidized bed. The reactor also includes a cooling system that removes polymerization heat and maintains the fluidized bed at a target temperature. The composition of the gas (such as ethylene, alpha-olefins and hydrogen) is fed into the reactor and is monitored in the circulation loop by an online gas chromatograph to maintain a specific concentration for controlling polymer properties. The spray-dried catalyst is fed into the reactor from a high pressure device in the form of slurry or dry powder, wherein the slurry is fed via an injection pump and the dry powder is fed via a metering disk. The catalyst enters the fluidized bed below 1 / 3 of the height of the fluidized bed. The polymerization system weighs the fluidized bed and includes an isolation port that discharges the polymerized product from the reactor vessel in response to the increase in weight of the fluidized bed as the polymerization reaction proceeds. The polymerization conditions for Inventive Example 2 (IE 2) are reported in Table 1.
[0091] Table 1 - Continuous polymerization reactor process data of Example 2 of the present invention (IE 2)
[0092] sample Internet Explorer 2 catalyst IE 1 Average reactor temperature [℃] 80.00 Average H2 / C2 molar ratio 0.000644 Average H2 / PPM / C2% ratio 6.438 Average H2 / C2 flow ratio (lb / hr) 0.056 Average C2PP [psi] 130.3 Average C2 flow (lb / hr) 64.964 Average C6 / C2 (molar ratio) 0.0002 Average C6 / C2 flow ratio 0.0008 Reactor pressure (psi) 350 Slurry catalyst feed rate (cc / hr) 11 Adjust solution feed (lb / hr) 0.0 Average stay time 2.67 Average bed weight [lb] 126.7261 Productivity (lb / lb) 10192
[0093] Six commercially available polymers were used as comparative examples: Comparative Example 1 (CE 1), a unimodal polymer DOW prepared using UCAT-J catalyst TMHDPE XDMDA-1227, density 0.952 g / cm3, melt index (I2) 2.7 dg / min; Comparative Example 2 (CE 2), unimodal polymer obtained from UNIVATION TECHNOLOGIES, prepared using VP-100 catalyst, density 0.952 g / cm3, melt index (I2) 3.72 dg / min. Comparative Example 3 (CE 3), bimodal polymer CONTINUUM prepared using UCAT-J catalyst TM DMDC-1270, density 0.955 g / cm3, melt index (I2) 2.5 dg / min; Comparative Example 4 (CE 4), bimodal polymer CONTINUUM prepared using UCAT-J catalyst TM DMDC-1250, density 0.955 g / cm3, melt index (I2) 1.5 dg / min. Comparative Example 5 (CE 5), unimodal polymer DOW prepared using UCAT-J catalyst TM DMDA-8904, density 0.952 g / cm3, melt index (I2) 4.4 dg / min. Comparative Example 6 (CE 6), unimodal polymer DOW prepared using UCAT-J catalyst TM DMDA-8907, density is 0.952g / cm3, melt index (I2) is 6.8dg / min.
[0094] Additional commercially available polymers were used to study the relationship between density and peak melting temperature: DOW TM HDPEKT 10000 (density 0.964g / cm 3 , melt index (I2) is 8dg / min), EVERCAP TM DMDB 1220 (density 0.958 g / cm 3 , melt index (I2) is 0.3dg / min), EVERCAP TM DMDA 1260 (density 0.963 g / cm 3 , melt index (I2) is 2.7dg / min), DOW TM DMDC 1210 (density 0.952g / cm 3 , melt index (I2) is 10dg / min), DOW TM DMDA 8920 (density 0.954 g / cm 3 , melt index (I2) is 20dg / min), DOW TM DMDA 8933 (density 0.950 g / cm 3, melt index (I2) is 33dg / min), DOW TM DMDA-8007 (density 0.965g / cm 3 , melt index (I2) is 8.3dg / min) and DOW TM DMDA 8940 (density 0.951 g / cm 3 , melt index (I2) is 44dg / min).
[0095] A number of properties were measured for the polymers. The results are reported in Tables 2-3. The melt index (I2) was determined according to ASTM D1238 (190°C, 2.16 kg), the melt index (I2) was determined according to ASTM D1238 (190°C, 10 kg), and the melt index (I 10 ), melt index (I 21 ). Density was determined according to ASTM D792. Mn, Mw, Mz, Mp and Mw / Mn were determined by GPC as discussed herein. Environmental stress crack resistance (ESCR) was determined in 10 vol% aqueous Igepal CO-630 solution according to ASTM D-1693, Method B. 50 Charpy impact strength was performed according to ISO 179; tensile properties (tensile yield strain, tensile yield stress, tensile secant modulus at 2%) were determined according to ASTM D638 (test speed was 2 in / min). Flexural properties (flexural modulus and flexural secant modulus at 2%) were determined according to ASTM D790 (test speed was 0.5 in / min and 0.05 in / min). Crystallization enthalpy, peak crystallization temperature, melting enthalpy and peak melting temperature were determined via differential scanning calorimetry as discussed herein.
[0096] Composition Conventional GPC
[0097] The chromatographic system consists of a PolymerChar GPC-IR (Valencia, Spain) high temperature GPC chromatograph equipped with an internal IR5 infrared detector (IR5). The autosampler oven chamber is set to 160°C, and the column chamber is set to 150°C. The columns used are 4 Agilent "Mixed A" 30cm 20 micron linear mixed bed columns. The chromatographic solvent used is 1,2,4 trichlorobenzene and contains 200ppm of butylated hydroxytoluene (BHT). The solvent source is nitrogen sparged. The injection volume used is 200 microliters, and the flow rate is 1.0 ml / min.
[0098] Calibration of the GPC column set was performed with 21 narrow molecular weight distribution polystyrene standards ranging from 580 g / mol to 8,400,000 g / mol and arranged in 6 "cocktail" mixtures with at least ten times intervals between individual molecular weights. Standards were purchased from Agilent Technologies. For molecular weights equal to or greater than 1,000,000, 0.025 g of polystyrene standards were prepared in 50 ml of solvent, and for molecular weights less than 1,000,000, 0.05 g of polystyrene standards were prepared in 50 ml of solvent. The polystyrene standards were pre-dissolved at 80°C with gentle stirring for 30 minutes, then cooled and the room temperature solution transferred to a 160°C autosampler dissolution oven to cool for 30 minutes. The polystyrene standard peak molecular weights were converted to polyethylene molecular weights using Equation 1 (as described in Williams and Ward, J. Polym. Sci., Polym. Let., 6, 621 (1968)):
[0099] M 聚乙烯 =A×(M 聚苯乙烯 ) B (Equation 1)
[0100] Where M is the molecular weight, A has a value of 0.4070, and B equals 1.0.
[0101] A fifth-order polynomial was used to fit the calibration points to the corresponding polyethylene equivalents.
[0102] Total plate counts for the GPC column set were performed with decane, which was introduced into the blank sample via a micro pump controlled by the PolymerChar GPC-IR system. The plate count of the chromatography system should be greater than 18,000 for 4 Agilent "Mixed A" 30 cm 20 micron linear mixed bed columns.
[0103] The samples were prepared semi-automatically using the PolymerChar "Instrument Control" software, where the target weight of the sample was set at 2 mg / ml and the solvent (containing 200 ppm BHT) was added to a septum-capped vial previously sparged with nitrogen via the PolymerChar high temperature autosampler. The samples were dissolved at 160°C for 2 hours under "low speed" shaking.
[0104] Based on the GPC results, using the internal IR5 detector (measurement channel) of the PolymerChar GPC-IR spectrometer, according to Equations 2-4, the PolymerChar GPCOne TMThe software was used to calculate the Mn value of the baseline-subtracted IR chromatogram at each equidistant data collection point (i) and the polyethylene equivalent molecular weight obtained from the narrow standard calibration curve at point (i) according to Equation 1. (GPC) 、Mw (GPC) and Mz (GPC) Calculation.
[0105]
[0106]
[0107]
[0108] To monitor deviations over time, a flow rate marker (decane) was introduced into each sample via a micropump controlled by the PolymerChar GPC-IR system. This flow rate marker (FM) was used to linearly correct the pump flow rate for each sample (Flow Rate (Nominal)) by comparing the RV of the corresponding decane peak in the sample (RV (FM Sample)) with the RV of the decane peak in the narrow standard calibration (RV (FM Calibrated)). Any changes in the decane marker peak time were then assumed to be related to a linear change in flow rate (Flow Rate (Effective)) throughout the run. After calibrating the system based on the flow marker peak, the effective flow rate (relative to the narrow standard calibration) was calculated as Equation 5. TM The software completes the processing of the flow marker peaks. An acceptable flow rate correction is such that the effective flow rate should be within + / - 0.5% of the nominal flow rate.
[0109] Flow rate (effective) = flow rate (nominal) x (RV (FM calibration) / RV (FM sample)) (Equation 5)
[0110] IR5 GPC Octene Composition Calibration
[0111] Calibration for IR5 detector dosing was performed using at least ten ethylene-based polymer standards (octene as comonomer) produced in a solution process (polyethylene homopolymer and ethylene / octene copolymer) from a single reactor over a single site metallocene catalyst, with narrow SCB distribution and known comonomer content (e.g., by 13C NMR method, Qiu et al., Anal. Chem.) 2009, 81, 8585-8589) in a solution process (polyethylene homopolymer and ethylene / octene copolymer) from a single reactor by a single-site metallocene catalyst, the known monomer content is in the range of from homopolymer (0 SCB / 1000 total C) to about 40 SCB / 1000 total C, where total C = carbon in the main chain + carbon in the branch chain. Each standard has a weight average molecular weight of 36,000 g / mole to 126,000 g / mole, as measured by GPC. The molecular weight distribution (Mw / Mn) of each standard is 2.0 to 2.5. The SCB standard polymer properties are shown in Table A.
[0112] Table A: "Copolymer" Standards
[0113] Comonomer weight % IR5 Area Ratio SCB / 1000Total C M Mw / Mn 23.1 0.2411 28.9 37,300 2.22 14.0 0.2152 17.5 36,000 2.19 0.0 0.1809 0.0 38,400 2.20 35.9 0.2708 44.9 42,200 2.18 5.4 0.1959 6.8 37,400 2.16 8.6 0.2043 10.8 36,800 2.20 39.2 0.2770 49.0 125,600 2.22 1.1 0.1810 1.4 107,000 2.09 14.3 0.2161 17.9 103,600 2.20 9.4 0.2031 11.8 103,200 2.26
[0114] The “IR5 Area Ratio” (or “IR5 Area Response”) of the “Baseline-Subtracted Area Response of the IR5 Methyl Channel Sensor” to the “Baseline-Subtracted Area Response of the IR5 Measurement Channel Sensor” was calculated for each of the “Copolymer” standards. 甲基通道面积 / IR5 测量通道面积 ”)” (including standard filters and filter wheels supplied by PolymerChar: Part No. IR5_FWM01 as part of the GPC-IR instrument). A linear fit of comonomer wt% frequency versus “IR5 Area Ratio” was constructed in the form of Equation 6 below:
[0115] Comonomer weight % = A0 + [A1 × (IR5 甲基通道面积 / IR5 测量通道面积 )] (Equation 6)
[0116] Where A0 is the "Comonomer wt%" intercept at "IR5 Area Ratio" of zero, and A1 is the slope of "Comonomer wt%" relative to "IR5 Area Ratio" and represents the increase in comonomer wt% as a function of "IR5 Area Ratio". For narrow PDI and narrow SCBD standard materials, the IR5 Area Ratio is equal to the IR5 Height Ratio.
[0117] Differential scanning calorimetry (DSC) can be used to measure the crystallinity of a sample over a wide temperature range at a given temperature. For example, a TA instrument (Discovery) equipped with an RCS (refrigeration cooling system) and an autosampler module is used to perform the analysis. During the test, a nitrogen purge gas flow of 50 mL / min was used. Each sample was pressed into a film and melted at a pressure of about 190°C; the molten sample was then air cooled to room temperature (about 25°C). A sample of 3 mg to 10 mg, 6 mm in diameter, was extracted from the cooled polymer, weighed, placed in a light aluminum pan (about 50 mg), and sealed with a gland. The analysis was then performed to determine its thermal properties. The thermal behavior of the sample was determined by ramping up and down the sample temperature to produce a heat flow to temperature curve. First, the sample was quickly heated to 180°C and kept isothermal for 5 minutes to remove its thermal history. Next, the sample was cooled to -40°C at a cooling rate of 10°C / minute and kept isothermal for 5 minutes at -40°C. The sample is then heated to 150°C at a heating rate of 10°C / min (this is the "second heating" ramp). A cooling curve and a second heating curve are recorded. The cooling curve is analyzed by setting a baseline endpoint from the start of crystallization to -20°C. The heating curve is analyzed by setting a baseline endpoint from -20°C to the end of melting. The peak crystallization temperature (Tc), heat of fusion (Hc) (also known as crystallization enthalpy) are determined from the first cooling curve. Heat of fusion (Hf) (also known as melting enthalpy) and peak melting temperature are reported from the second heat curve.
[0118] Flexural testing was performed according to ASTM D790. Polymer pellet samples were compression molded to a nominal thickness of 0.125 inches at 190°C according to ASTM D4703 Procedure C as per Appendix A.1. The samples were conditioned at 23 (± 2)°C and 50 (± 10)% RH for at least 40 hours. The sample geometry (length, depth, thickness) was 5"×0.5"×0.125". For ASTM, the samples were tested in a flat position with a span of 2". The test speed was such that the flexural strain rate was 1% / min, which translates to 0.05in / min. In addition, the test allowed a strain rate of 10% / min. Based on the stress-strain data obtained, the flexural modulus is reported based on the initial slope of the curve. The secant modulus at 1% and 2% is reported as the slope of the line from the origin to 1% and 2% strain, respectively.
[0119] Tensile testing was performed according to ASTM D638. Polymer samples were compression molded to a nominal thickness of 0.075 inches (Type IV geometry) at 190°C according to ASTM D4703 Procedure C as per Appendix A.1. Type IV samples were die cut from sheets and conditioned at 23 (± 2)°C and 50 (± 10)% RH for at least 40 hours. Type IV samples were tensile tested according to D638 (Standard Test Method for Tensile Properties of Plastics) and D4976 (Standard Specification for Polyethylene Plastic Molding and Extrusion Materials). The test speed was 2" / in or 20" / min crosshead displacement. Strain was measured using an extensometer attached to the sample with an initial gauge length of 1 inch. Modulus measurements were performed using the slope of the initial portion of the stress-strain curve.
[0120] Environmental Stress Crack Resistance (ESCR) testing was performed according to ASTM D1693. Pellets were compression molded to the desired nominal thickness (0.0755" for Condition B) at 190°C according to ASTM D4703 Procedure C per Appendix A.1. D1693 tests the sample. The compression molded sheet is adjusted at 23°C (± 2°C) and 50%RH (± 10%RH), and a single specimen is punched out within 24 hours of molding using a suitable mold. The sample thickness is measured to ensure that they are within the ASTM specification of the appropriate condition B. The sample is further adjusted at 23°C (+ / -2°C) and 50%RH (+ / -5%RH), and tested at least 40 hours after compression molding and within 96 hours of compression molding. Immediately before the test, the sample is slotted to the desired depth, and then bent and loaded into the sample holder. The holder is then placed in a test tube, and the test tube is filled with an Igepal solution (10%) of an appropriate concentration. The tube is sealed and placed in a temperature-controlled water bath at 50°C. During the first week of the test, the cracks of the sample are observed twice a day, and then they are observed once a day. F50 is calculated based on a graphical method, but it is automatic in a spreadsheet.
[0121] Charpy test is carried out according to ISO 179. The sample is made of compression molded sheet. For compression molding, the pellet sample is molded to a nominal thickness of 4mm at 190°C. The pellet is weighed and placed in an appropriate picture frame slot. The slot has a Mylar peel sheet on each side and has a copper or brass plate backing. The sample is placed in a hot press for 4 minutes under low contact pressure (3,000psi), and then placed under high pressure (30,000psi) for another 6 minutes. Thereafter, the sample is cooled at 15°C / min (+ / -2°C / min) until the sample is at about 35°C, at which time it is removed from the press. A sample is cut from the sheet using an appropriate mold to obtain a sample with a length of 80mm and a width of 10mm. The sample is slotted on the long side in the thickness direction using an automated slotter to leave a ligament width of 8mm. The slotting half angle is 22.5° and the radius of curvature at the top is 0.25mm. The samples were conditioned at 23°C + / - 2°C and 50% + / - 10% RH for at least 40 hours. For samples tested at non-ambient temperatures, the samples were further conditioned at the test temperature for a minimum of 1 hour. The samples were loaded into a Charpy Izod tester with the notch away from the impactor. The pendulum was released and the energy absorbed during the test was automatically recorded. The samples were checked after the test and the type of failure (complete, hinged, partial or unbroken) was recorded. Each sample was tested ten times at each temperature.
[0122] The resin designs of the inventive examples provide excellent tensile properties. As shown in Table 2, IE 2 shows a better tensile yield stress than CE 2, which has comparable I2 and density but does not have the molecular weight distribution of the present invention. Notably, the unimodal resin IE 2 even shows better yield stress than two prior art bimodal resins CE 3 and CE 4.
[0123] The resin design of the inventive examples provides excellent ESCR performance when compared to unimodal resins of similar I2 and density. IE 2 shows better ESCR than CE 1 and CE 2, which can be attributed to the positive broad orthogonal composition distribution (BOCD), which indicates a relatively large reverse comonomer distribution value.
[0124] The innovative resin design of IE 2 also results in high Charpy impact strength, which can be seen from the comparison between IE 2 and CE 5. IE 2 and CE 5 share similar Mw (97436 vs. 87829), while IE 2 exhibits almost twice the Charpy impact strength measured at 0°C. CE 4 is a bimodal resin with comparable I2 and density, however, IE 2 shows better Charpy impact strength than the unimodal resin. It is worth noting that it is very challenging for a unimodal resin to outperform a bimodal resin in terms of mechanical properties.
[0125] The unique resin structure disclosed herein also results in a very high peak melting temperature. Typically, the peak melting temperature of a high density polyethylene is determined by its density ( Figure 1 and Table 3), but IE 2 is a clear outlier. The peak melting temperature of IE 2 is higher than other resins with similar density (e.g., DMDA 8920, DMDC 1210). The peak melting temperature of IE 2 is even higher than that of DMDA 1260, which has a density 0.01 g / cm higher than IE 2. 3 .
[0126] Table 2 - Polymer properties
[0127]
[0128]
[0129] Table 3 - Density and peak melting temperature relationship of existing resins
[0130] Example <![CDATA[Density (g / cm 3 )]]> Peak melting temperature (℃) Internet Explorer 2 0.955 133.3 KT 10000 0.964 132.9 DMDB 1220 0.958 131.4 CE 4 0.955 129.9 CE 3 0.955 130.2 DMDA 1260 0.963 132.2 DMDC 1210 0.952 129.3 CE 2 0.952 131.2 CE 5 0.952 130.2 CE 6 0.951 129.4 CE 1 0.952 131.3 DMDA 8920 0.954 129.1 DMDA 8933 0.950 127.4 DMDA 8007 0.965 133.3 DMDA 8940 0.951 127.4
Claims
1. A method of forming a closure device, the method comprising: A high-density polyethylene (HDPE) resin is provided, wherein the high-density polyethylene (HDPE) resin has: 0.950g / cm 3 Up to 0.960g / cm 3 density; According to ASTM Melt index (I2) of 1.000 dg / min to 5.000 dg / min measured by D1238 (190°C, 2.16 kg); Mn 25,000 to 45,000; 80,000 to 125,000 Mw; 180,000 to 350,000 Mz; and Molecular weight distribution Mw / Mn of 2.5 to 3.5; Molecular Weight Comonomer Distribution Index (MWCDI) > 0.2; and The closure device is formed using the HDPE resin.
2. The method according to claim 1, wherein the HDPE resin has a strength of greater than 5 kJ / m 2 Up to 15kJ / m 2 Charpy impact value (-40℃).
3. The process of any one of claims 1 to 2, wherein the HDPE has a peak melting point (Tm) greater than 132°C.
4. The method of any one of claims 1 to 3, wherein the HDPE has an average tensile yield stress of 3.8 ksi to 4.2 ksi (2 in / min test speed).
5. The method according to any one of claims 1 to 4, wherein the HDPE resin has an environmental stress crack resistance (ESCR) condition B (F50, 10%)。 6. The method of any one of claims 1 to 5, wherein the HDPE resin has a tensile secant modulus at 2% of 110 ksi to 140 ksi.
7. The method of any one of claims 1 to 6, wherein the HDPE resin has a tensile yield strain (2 in / min) of 9% to 11%.
8. The method of any one of claims 1 to 7, wherein the HDPE resin has an average flexural modulus (0.05 in / min) of 150 to 200 ksi.
9. The method of any one of claims 1 to 7, wherein the HDPE resin has an average flexural modulus (0.5 in / min) of 190 ksi to 230 ksi.
10. The method of any one of claims 1 to 7, wherein the HDPE resin has a flexural secant modulus at 2% (0.05 in / min) of 100 ksi to 140 ksi.
11. The method of any one of claims 1 to 7, wherein the HDPE resin has a flexural secant modulus at 2% (0.5 in / min) of 120 ksi to 170 ksi.
12. The method according to any one of claims 1 to 11, wherein the HDPE resin has a melt index (MI) of 5 dg / min to 40 dg / min as measured according to ASTM D1238 (190° C., 10 kg). 10 ).
13. The process of any one of claims 1 to 12, wherein the HDPE resin has a polydispersity composition index (PCI) >5.
14. The method of any one of claims 1 to 13, wherein forming the closure device comprises compression molding or injection molding the HDPE resin to form the closure device.
15. A method for preparing a HDPE resin according to any one of claims 1 to 14, the method comprising: Preparation of catalyst compositions using asymmetric hafnium metallocenes; and contacting the catalyst composition with ethylene and optionally a comonomer selected from the group consisting of propylene and (C4-C20) α-olefins to prepare the HDPE resin.
16. A method for preparing a HDPE resin according to any one of claims 1 to 14, the method comprising: The catalyst composition was prepared using an asymmetric hafnium metallocene having an n-propylcyclopentadienyl ligand represented by structure (I): Where R 1 n-propyl; and each X is independently a leaving group; and The catalyst composition is contacted with ethylene and optionally a comonomer selected from the group consisting of propylene and (C4-C20) α-olefins to prepare the HDPE resin.
17. A closure device formed by the method according to any one of claims 1 to 16.
18. A closure device according to claim 17, wherein the closure device is a screw cap.
Citation Information
Patent Citations
Method for synthesis of monocyclopentadienyl complexes of zirconium and hafnium
WO2016168448A1